Determination of certain VOCs in paints and architectural coatings by dynamic headspace gas chromatography-mass spectrometry. Issue 35 (12th August 2021) - Alderman, Nicholas P.; Courville, Matthew; Tokarczyk, Ryszard
Abstract : A quantitative method for the determination of VOCs in paints was developed in support of Environment and Climate Change Canada's Automotive Refinishing Product and Architectural Coatings VOC Concentration Limits regulations. Abstract : A quantitative method for the determination of the following VOCs: acetone, dichloromethane, dimethyl carbonate, methyl acetate, tertiary butyl acetate, chlorobenzotrifluoride (4-CBTF) and propylene carbonate in paints was developed in support of Environment and Climate Change Canada's Automotive Refinishing Product and Architectural Coatings VOC Concentration Limits regulations. These compounds are excluded from the VOC definition by Canadian Environmental Protection Act (CEPA) regulations, and their content do not contribute to the overall VOC content in products for regulatory purposes. The method is based on Dynamic Headspace GC-MS. It was determined that activated carbon is the best trapping medium for these compounds. The technique has been compared to a currently used direct injection technique, with comparable results. Contrary to the direct injection method which requires complex sample handling prior to injection in the gas chromatograph, the dynamic headspace method practically eliminates the need for sample handling allowing for much shorter sample turnover and reducing the possibility of sampling handling errors.